Staff Guidance Note on the Fund's Engagement with Small Developing States. (Policy Papers; Policy Paper ;, 2014)
This note highlights the unique economic characteristics and constraints facing small developing states. It provides operational guidance on Fund engagement with such countries, including on how small country size might influence the use of Fund facilities and instruments, program design, capacity building activities, and collaboration with other institutions and donors. The guidance note draws on the March 2013 Board papers on small states and the associated Executive Board discussion. The findings of the paper and implications for Fund engagement with small states were presented to small states authorities during the 2013 Annual Meetings, as well as in regional IMF conferences with small states in the Bahamas (September 2013) and Vanuatu (November 2013). Series.